Evaluation of EBV transformation of human memory B-cells isolated by FACS and MACS techniques. (3rd July 2016) - Sadreddini, Sanam; Jadidi-Niaragh, Farhad; Younesi, Vahid; Pourlak, Tala; Afkham, Amir; Shokri, Fazel; Yousefi, Mehdi
Abstract: Several studies have been performed to develop effective neutralizing monoclonal antibodies. The Epstein–Barr virus (EBV) can efficiently immortalize B-cells to establish lymphoblastoid cell lines (LCL) and so it has been used extensively for transformation of B-cells to produce and secrete immunoglobulin. The present study addressed the effect of TLR7/8 agonist (R848), feeder cells layer and ﬂuorescence-activated cell sorting (FACS) and magnetic-activated cell sorting (MACS) cell separation methods on the transformation efficiency of antibody-producing memory B-cells. For these studies, the antigen used for analyses of antibody formation was the tetanus neurotoxin (TeNT) derived from Clostridium tetani . The results here showed that employing an HFFF.PI6 feeder cell layer, R848 agonist and FACS-mediated purification of memory B-cells led to increased transformation efficiency. Altogether, the effects of the R848 and the feeder cells provided an efficient method for EBV transformation of human B-cells. Moreover, there was an advantage in using FACS sorting of B-cells over the MACS method in the context of EBV transformation and immortalization of precursors of antigen-specific B-cells.